Penggunaan Strategi Struktural dan Semantik Dalam Terjemahan Cerita Rakyat Jepang “Donguri dan Kucing Hutan” Karya Antonius Pudjo - Febi Ariani Saragih (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2017)
AbstractIn the world of translation, translators can use a variety of strategies. One is the structural and semantic strategy. This research discusses the method of translation by using the structural and semantic strategy of Japanese folk literature translated by Antonius Pudjo. There are three basic strategies related to structural issues, namely addition, subtraction, and transposition. As for the semantic strategy there are 9 strategies: levy, cultural equivalent, descriptive equivalent and component analysis, synonym, official translation, depreciation and expansion, addition, deletion, and modulation. This research is qualitative descriptive research. Research data is the translation of the story "Donguri and Kucing Hitam" in which using the structural and semantic strategy in the process of translation. Technique of collecting data is using documentation technique of read-record. While the technique of data analysis is done by analyzing one by one each translation from source language, then analyzed whether using structural or semantic strategy, and classified by type. From the 14 sentences taken as data, it is known that on the structural strategy found transposition strategy 6 sentences, semantic strategy found semantic strategy of adding and synonyming each 5 sentences, deletion 4 sentences, modulation 2 sentence, and levy 1 sentences. Of the 7 sentences used as data in uncovering the implicit meaning contained in the folklore, it is known that there is 1 referential meaning, 2 meanings of linguistic context, and 4 situational meanings. Not too much data is obtained, because besides the source language has made the sentences clearly, chances are also the translator wants the reader to enjoy the literary works as the original form. Antonius translation is good and the language is accepted by target language. In terms of grammatical, there are not many changes made by the translator, and can be categorized as loyal to resource language but idiomatic and communicativeKey Words: structural strategies, semantic strategies, translating, Japanese children story